Left ventricular ejection fraction and contrast induced acute kidney injury in patients undergoing cardiac catheterization: Results of retrospective chart review - Ajam, Firas; Maludum, Obiora; Ugoeke, Nene; Mahida, Hetavi; Alrefaee, Anas; DNP, Amy Quinlan; NP, Jennifer Heck-Kanellidis; DO, Dawn Calderon; Hossain, Mohammad A; Asif, Arif (Journal of Cardiology and Cardiovascular Medicine, 2019)
Background: Contrast-induced acute kidney injury (CI-AKI) is an important cause of increasing the hospital stay and in-hospital mortality. By increasing intra-renal vasoconstriction, left ventricular ejection fraction (LVEF) can increase the risk of CI-AKI. We sought to investigate whether LVEF can impact the incidence of CI-AKI after cardiac catheterization and whether it can be used to predict CI-AKI. Methods: Patients underwent cardiac catheterization from December 2017 to February 2018 at Jersey Shore University Medical Center were enrolled in the study. Contrast-induced acute kidney injury (CI-AKI) was defined as an increase in serum creatinine of ≥ 0.5 mg/dL or an increase of ≥ 25% from the pre-procedure value within 72 hours post-procedure. The maximum allowable contrast dose was calculated using the following formula: (5* (weight (kg)/creatinine level (mg/dL)). A multivariable logistic regression analyses, controlling for potential confounders, were used to test associations between LVEF and CI-AKI. Results: 9.6% had post catheterization CI-AKI. A total of 18 out of 44 (44%) of patients who had CI-AKI also had ongoing congestive heart failure. No statistically significant association found neither with maximum allowable contrast (p = 0.009) nor ejection fraction (p = 0.099) with the development of CI-AKI. Conclusion: In spite of the fact that no statistically significant relationship found between the percentage maximum contrast dose and the ejection fraction with the post-procedure CI-AKI, we heighten the essential of employing Maximum Allowable Contrast Dose (MACD) and ejection fraction in patients undergoing PCI to be used as a clinical guide to predict CI-AKI.